VLTI/GRAVITY Provides Evidence the Young, Substellar Companion HD 136164 Ab Formed Like a “Failed Star” - William O. Balmer; L. Pueyo; S. Lacour; J. J. Wang; T. Stolker; J. Kammerer; N. Pourré; M. Nowak; E. Rickman; S. Blunt; A. Sivaramakrishnan; D. Sing; et al. (The Astronomical Journal, 2024)
Young, low-mass brown dwarfs orbiting early-type stars, with low mass ratios ( q ≲ 0.01), appear to be intrinsically rare and present a formation dilemma: could a handful of these objects be the highest-mass outcomes of “planetary” formation channels (bottom up within a protoplanetary disk), or are they more representative of the lowest-mass “failed binaries” (formed via disk fragmentation or core fragmentation)? Additionally, their orbits can yield model-independent dynamical masses, and when paired with wide wavelength coverage and accurate system age estimates, can constrain evolutionary models in a regime where the models have a wide dispersion depending on the initial conditions. We present new interferometric observations of the 16 Myr substellar companion HD 136164 Ab (HIP 75056 Ab) made with the Very Large Telescope Interferometer (VLTI)/GRAVITY and an updated orbit fit including proper motion measurements from the Hipparcos–Gaia Catalog of Accelerations. We estimate a dynamical mass of 35 ± 10 M _J ( q ∼ 0.02), making HD 136164 Ab the youngest substellar companion with a dynamical mass estimate. The new mass and newly constrained orbital eccentricity ( e = 0.44 ± 0.03) and separation (22.5 ± 1 au) could indicate that the companion formed via the low-mass tail of the initial mass function. Our atmospheric fit to a SPHINX M-dwarf model grid suggests a subsolar C/O ratio of 0.45 and 3 × solar metallicity, which could indicate formation in a circumstellar disk via disk fragmentation. Either way, the revised mass estimate likely excludes bottom-up formation via core accretion in a circumstellar disk. HD 136164 Ab joins a select group of young substellar objects with dynamical mass estimates; epoch astrometry from future Gaia data releases will constrain the dynamical mass of this crucial object further.